Polarographic Study of Cu-pyramidone in Aqueous-Nonaqueous Medium from Soil Ore Sample of Khetri Nagar - Sharma, Jaswant; Mukherjee, S.K. (Asian Journal of Chemistry, 2010)
In the present paper, polarographic aqueous-nonaqueous medium study of Cu-pyramidone in soil ore sample collected from the vicinity of Khetri copper project by using a solution containing 1 mM copper nitrate from ore and different concentrations of pyrarnidone in 0.1 M NaCIO4 solution was performed.